PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PT. DEMPO LASER METALINDO SURABAYA - ARIF WIBOWO, KUKUH (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2014)
ABSTRACT Job satisfaction does not come by itself. Besides the will and effort of the employees themselves, job satisfaction is also influenced by the conditions of work environment. The work environment in a company is essential to be considered by the management of the company. This is because a conducive working environment may bring several benefits for the company, for instance the emerge of job satisfaction that will directly affect to the productivity. Thus, this thesisis written to find out the influence of work environment conditions toward job satisfaction of the employees, especially at PT Dempo Laser Metalindo Surabaya. The population in this study were all employees of PT. Dempo Laser Metalindo Surabaya. To determine the sample, the researcherwas using saturated sample method, so that in the end a total of 100 people were acquired as the sample of the research. This research included in the associative research using a quantitative approach. Statistical instruments used in this research were a simple regression analysis, correlation, meanwhile the determination and hypothesis testing was done through SPSS 17 for windows. Variables used in this research werethe condition of work environment as the independent variable (X), andjob satisfaction as the dependent variable (Y). The results of this study indicate that the conditions of the work environment affect the job satisfaction of the employees about 46.3%. Meanwhile the other 53.7% is influenced by other factors that are not used in this research.Keywords: Work Environment, Job Satisfaction